PENANAMAN NILAI-NILAI AKHLAQUL KARIMAH PESERTA DIDIK DALAM MENANGGULANGI PENGARUH NEGATIF DI ERA GLOBALISASI DI SEKOLAH MENENGAH ATAS ISLAM ALMAARIF SINGOSARI MALANG - Fiqri Imam Ansyori; Azhar Haq; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Many researches on the development of akhlaqul karimah have been carried out, but the internalization of Islamic values in its development has yet to be determined. This research aims to increase the knowledge and roles of students, parents, teachers and the community in overcoming negative influences in the era of globalization starting at the family, school and community levels. Using case study research, and in-depth interviews with two high school teachers Amaarif Singosari Malang, and analyzing with qualitative analysis. Research results; in intracurricular activities, among others, planning teachers, creating learning units, carrying out teaching activities. In the extracurricular field, including congregational prayers, Dhuhr Prayers at Almaarif Singosari High School, Commemoration of Islamic Holidays in commemoration of Islamic holidays, Duha Prayers, Ramadhan Islamic Boarding School. And the inhibiting factors include the lack of religious education for students' parents, there are still students who are less aware of doing religious activities, less supportive facilities, information technology, and the environment. The results of this study require Islamic religious education teachers to foster the morals of students to apply, practice and direct moral development so that the essence or learning of akhlaqul karimah itself is used in the daily lives of students as well as the growth of innovative thinking and creativity.